2018
DOI: 10.3390/toxins10040155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota and Diet on Uremic Retention Solutes Production in the Context of Chronic Kidney Disease

Abstract: Uremic retention solutes (URS) are associated with cardiovascular complications and poor survival in chronic kidney disease. The better understanding of the origin of a certain number of these toxins enabled the development of new strategies to reduce their production. URS can be classified according to their origins (i.e., host, microbial, or exogenous). The discovery of the fundamental role that the intestinal microbiota plays in the production of many URS has reinstated nutrition at the heart of therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 82 publications
0
52
1
1
Order By: Relevance
“…Thus, whether these microbes play a crucial role on the development of hypertension via mediating the TMA−TMAO metabolic pathway in children with early-stage CKD deserves further clarification. Of note is that a key factor in determining gut microbiota composition is the type of diet in patients with CKD [46]. Since the Mediterranean diet that is rich in fiber has been proven to reduce cardiovascular risk [47], it can be speculated that high-fiber dietary intervention might be an efficient way to control microbiota to further prevent CVD in CKD children [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whether these microbes play a crucial role on the development of hypertension via mediating the TMA−TMAO metabolic pathway in children with early-stage CKD deserves further clarification. Of note is that a key factor in determining gut microbiota composition is the type of diet in patients with CKD [46]. Since the Mediterranean diet that is rich in fiber has been proven to reduce cardiovascular risk [47], it can be speculated that high-fiber dietary intervention might be an efficient way to control microbiota to further prevent CVD in CKD children [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increased urea levels in patients with CKD and favorable alteration of the gut microbiome can lead to an increase in permeability and alterations of the intestinal epithelial barrier [92]. For this reason, it is necessary to preserve the quality of the gut microbiome through the diet; namely by introducing the right amount of protein and fiber [184]. It has also been observed that a VLPD diet reduced PCS levels by about 30-35% in CKD patients after only one week of dietetic treatment [94].…”
Section: The Importance Of Nutritional Therapy During Ckdmentioning
confidence: 99%
“…The range of potential intervention spans from diet modification to population-level education efforts regarding the potential impact of food supplements to reducing uremic toxin generation rate and intestinal absorption, modifying the microbiome or design of interventions to limit toxin actions, such as targeting the AhR [ 9 , 136 , 137 ]. A detailed discussion of modulation of uremic toxins is provided by Koppe et al in this issue [ 138 ]. In this regard, some drugs successfully tested preclinically in culture or in vivo, are already in clinical use, although sometimes for a different indication.…”
Section: The Way Forwardmentioning
confidence: 99%